Profile of Green Chemistry on Chemistry Education Students: Study on Developing Green Chemistry Practical Module to Support Sustainable Development Goals (SDGs) - Mutiara Dwi Cahyani; Tania Avianda Gusman; Ari Yustisia Akbar (Jurnal Penelitian Pendidikan IPA, 2024)
The Society 5.0 era emphasizes production efficiency by transitioning from conventional to renewable energy sources. Thus, the Society 5.0 Era aligns with one of the goals of the SDGs, which is that industrial processes become more environmentally friendly and more efficient in using energy resources while increasing their value. Green chemistry is a comprehensive approach that designs safe chemicals ranging from environmentally friendly chemical products and processes to reducing the formation of harmful chemical substances. The type of research is descriptive and aimed at describing the student's early understanding of green chemistry. The subject of this study is a student of Prodi Education Chemistry at the University of Muhammadiyah Cirebon. The test instrument consists of 4 description questions compiled to measure the student's initial understanding of green chemistry. The analysis results show that the students understood the terminology for green chemistry. However, students still need to understand the 12 principles of green chemistry and their applications in everyday life.